2018
DOI: 10.1136/esmoopen-2018-000425
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Nutritional Index as an independent prognostic factor in locoregionally advanced squamous cell head and neck cancer

Abstract: BackgroundLocally advanced head and neck squamous cell carcinoma (LAHNSCC) is a heterogeneous disease in which better predictive and prognostic factors are needed. Apart from TNM stage, both systemic inflammation and poor nutritional status have a negative impact on survival.MethodsWe retrospectively analysed two independent cohorts of a total of 145 patients with LAHNSCC treated with induction chemotherapy followed by concurrent chemoradiotherapy at two different academic institutions. Full clinical data, inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
41
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(46 citation statements)
references
References 26 publications
5
41
0
Order By: Relevance
“…Thrombocytosis may dampen the recognition and cytotoxicity of tumor cells by immune cells [28] or promote tumor growth by stimulating tumor angiogenesis, vascular invasion, and distant metastasis [32,33]. Our results reinforce the predictive values of PNI and PLR seen in previous retrospective studies, which showed that the PNI predicted overall survival and treatment-related toxicities in LAHNC patients [22,34] and that the PLR predicted survival outcomes and disease recurrence in HNC patients [35][36][37]. Moreover, this study demonstrated that the combination of these two parameters provided better prediction of one year mortality in LAHNC patients.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Thrombocytosis may dampen the recognition and cytotoxicity of tumor cells by immune cells [28] or promote tumor growth by stimulating tumor angiogenesis, vascular invasion, and distant metastasis [32,33]. Our results reinforce the predictive values of PNI and PLR seen in previous retrospective studies, which showed that the PNI predicted overall survival and treatment-related toxicities in LAHNC patients [22,34] and that the PLR predicted survival outcomes and disease recurrence in HNC patients [35][36][37]. Moreover, this study demonstrated that the combination of these two parameters provided better prediction of one year mortality in LAHNC patients.…”
Section: Discussionsupporting
confidence: 88%
“…BMI was defined as weight in kilograms divided by height in meters squared (kg/m 2 ); BWL was calculated as (BW at diagnosis -ideal BW)/ideal BW × 100%. The laboratory nutrition indexes were calculated as follows: PNI, 10 × serum albumin (g/dL) + 0.005 × total lymphocyte count (TLC) (/mm 3 ), and NRI, 1.519 × serum albumin (g/L) + 41.7 × (initial BW/ideal BW) [22,23]. The NRI scores were classified into severe (< 83.5), moderate (83.5-97.5), mild (97.5-100), and no malnutrition (> 100) risk groups [23].…”
Section: Malnutrition Assessment Methodsmentioning
confidence: 99%
“…However, there have been few studies that have described the prognostic significance of OPNI for patients with head and neck cancer who undergo radiotherapy or chemoradiotherapy [ 23 ]. Although Bruixola et al reported that OPNI is an independent prognostic factor in locoregionally advanced squamous cell head and neck cancer who undergo chemoradiotherapy following induction chemotherapy [ 24 ]; to the best of our knowledge, our study is the first to report the prognostic value of OPNI in patients with OSCC who undergo definitive CRT. The results of the present study are also in line with current evidence, suggesting that OPNI could be useful for guiding treatment decisions for patients with OSCC undergoing chemotherapy and/or radiotherapy.…”
Section: Discussionmentioning
confidence: 82%
“…A multimodal treatment approach with a combination of surgery and non‐surgical/conservative treatment (ie, radiation, chemotherapy) is associated with extensive surgical wounds and mucositis which impairs the ability for oral food intake . Although there is an abundance of proposed clinical and laboratory parameters, there is still no general consensus how to best assess the nutritional status and consequently stratify the risk for malnutrition. Several studies for instance have shown that a low BMI is associated with poor overall survival .…”
Section: Introductionmentioning
confidence: 99%